ISOLATION, SCREENING OF PHYTATE DEGRADING FUNGI (ASPERGILLUS NIGER) AND OPTIMIZATION OF SUBMERGED FERMENTATIVE PRODUCTION OF PHYTASE - CH.M.KUMARI CHITTURI; P. JEEVANA LAKSHMI (International Journal of Pharma and Bio Sciences, 2016)
Microbial phytases are having several applications and one of the important application is it can be used as an animal feed supplement, not only to improve phytate digestibility and nutritive value of plant based foods but also reduces the environmental phosphorus pollution. In the present study, 12 fungal strains were isolated from different poultry soil wastes (Tirupati & surrounding areas) and screened for phytase activity by using phytase screening medium (PSM). Among the isolates one strain was found to possess potent phytase producing activity and identified as Aspergillus niger which has been selected for further studies. Phytase production by A.niger was evaluated in submerged fermentation. Effect of different culture media on phytase production was assessed and fermentation parameters were optimized. Physical parameters (temperature, pH), chemical parameters (different carbon and nitrogen sources and mineral salts) Optimization studies were studied. Maximum phytase activity of 465 U/ml was found at 30°C in submerged cultivation. The activity was found to decline above 30°C. The fungus failed to grow above 50°C. Phytase was most active at pH 5 (456 U/ml) with an increase in the pH of the medium enzyme activity declined. Optimization studies indicated that glucose was more suitable carbon source for maximum (478 U/ml) phytase production. Various nitrogen sources were used in optimization process where peptone has exhibited maximum activity of 482U/ml. It was found in our results that all the metal salts (sodium chloride, magnesium sulphate, manganese sulphate and copper sulphate) used in the study had a negative impact on the enzyme production.